2018
DOI: 10.12944/carj.6.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic Analysis Based on Energy Input and Output of Mixed Cropping Systems of Bhabhar Region (Shiwalik Range of Kumaun Himalaya, India)

Abstract: In the present study, the status of energy efficiency and economy of existing agroecosystems in the Shiwalik range of Kumaun Himalaya were assessed. A large number of plant species were cultivated/maintained by the local inhabitants to conserve the diversity in agroecosystems. Agriculture was the main source of economy of the villagers. The agroforestry system provides many ecological services to enhance the socio-economic condition of the farmers. In addition, home garden is another land use system, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
(25 reference statements)
3
6
0
Order By: Relevance
“…used. Consumption of human and bullock labor in present study were comparable to energetic values reported by several workers for different agroecosystems of the region ( Bisht et al., 2021 ; Padalia et al., 2018 ). The quantities of seed inputs recorded in our study were relatively highest in high altitude farms.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…used. Consumption of human and bullock labor in present study were comparable to energetic values reported by several workers for different agroecosystems of the region ( Bisht et al., 2021 ; Padalia et al., 2018 ). The quantities of seed inputs recorded in our study were relatively highest in high altitude farms.…”
Section: Discussionsupporting
confidence: 90%
“…The total input energy recorded in present study were in line with the reported range from 556000-920000 MJ ha −1 yr −1 by Bagwari and Todaria (2011) to 1921000–3433000 MJ ha −1 by Kumar (2011) along the altitudinal gradient of Central Himalaya. The energy input values were also comparable to input values reported by similar studies on different land use systems of the region ( Bisht et al., 2021 ; Padalia et al., 2018 ; Parihaar et al., 2015 ).…”
Section: Discussionsupporting
confidence: 87%
“…Agroforestry plays the most important role in increasing agricultural productivity by nutrient recycling, improving soil fertility, increasing the percentage of the soil nutrient, reducing soil erosion, and enhancing farm income than does conventional crop production (S. S. Bargali et al, ). Furthermore, it has promising potentials for reducing deforestation while increasing food, fodder, and fuel wood production (Padalia et al, ). Agroforestry can be a better climate change mitigation option than ocean, and other terrestrial option, because of the secondary environmental benefits such as food security and secured land tenure, increasing farm income and restoring and maintaining watershed hydrology and soil conservation (Kürsten & Burschel, ).…”
Section: Discussionmentioning
confidence: 99%
“…The different land use systems of the Kumaun Himalaya vary enormously in their structural complexity and species diversity, their productive and protective attributes, and their socioeconomic dimensions. In the Kumaun Himalayan region, a total of six land use systems were commonly practiced (Padalia, Bargali, Bargali, & Parihaar, ; Parihaar, ), namely, (a) sole cropping system (herbaceous crop only); (b) agri‐horticulture systems (herbaceous crops + fruit trees); (c) agri‐silviculture system (herbaceous crops + fuel/fodder/timber trees); (d) agri‐horti‐silviculture system (herbaceous crops + fruit trees + fuel/fodder/timber trees); (e) agri‐silvi‐pastoral system (grasses + trees + shrubs); and (f) home garden (HG; vegetable crops + fuel or fodder trees + multipurpose tree + ornamental plants + shrubs).…”
Section: Introductionmentioning
confidence: 99%
“…This in turn induces high soil loss, runoff, and input cost along with decreased farm productivity of introduced crop varieties with each passing years of cultivation [90][91][92][93][94]. Traditional agroforestry ecosystems, which are the source of many useful ESS [95], are being abandoned due to the outmigration of the male population, resulting in demographic changes and the conversion of agricultural land into permanent fallow [96]. Although many studies have discussed the state and dynamics of LULC change and their causes in western Himalayan region, little attention was given to address the impacts of such changes on various ecosystem services flowing out of this region.…”
Section: Impact Of Land Use and Land Cover Change On Ecosystem Servicmentioning
confidence: 99%